Crime scene investigation through DNA traces using Bayesian networks - Andrade, M.; Ferreira, M. A. M. (Aplimat - Journal of Applied Mathematics, 2014)
The use of biological information in crime scene identification problems is becoming more and more common. In this work, a crime scene is presented and used to exemplify the use of Bayesian networks, to analyse the information contained in a mixture DNA trace, referring to a crime in which there are two victims’ and two suspect’s involved. It is also made some discussion about the hypotheses to be considered in order to make them compatible with the possible information extracted from the mixture trace that constitutes the evidence.